Subdivision surface techniques - Mohamad, lklima (Penerbit UTM, 2007)
In geometric modeling, we always want our geometric model to looks as realistic as the real world. In this respect, the smoothness characteristics always come first. Thus, what kind of technique allows us to produce smooth modeling? The best approach is subdivision surface technique. In general, subdivision surface is a way to represent polygonal model is smoothly. In order to produce smooth surfaces, our main interest is the curvature at the surface. Implementation of subdivision technique to 3D model is quite straightforward and fast (DeRose.T et al 1998).